THE HISTORY OF THE DEVELOPMENT OF CRIMINAL COURTS IN UZBEKISTAN - Ilxomovna , Gulnoza Yusupdzhanova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The judicial system in Uzbekistan has undergone significant transformations from ancient times to the Soviet era, reflecting shifts in cultural, political, and legal frameworks. Early judicial practices in Central Asia were deeply rooted in indigenous traditions and religious doctrines, notably reflected in texts such as the